Modification of the American Public Health Association Procedure for Counting Yeast and Mold in Cottage Cheese - Powers, E. M. (1971)
The American Public Health Association method for counting low numbers of yeast and mold in cottage cheese was unsatisfactory due to altered pH of the culture medium. A modification of this method is presented.